2018
DOI: 10.1007/s10143-018-0979-4
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes following surgery in subgroups of comatose and very elderly patients with chronic subdural hematoma

Abstract: Increasing age and lower pre-operative Glasgow coma score (GCS) are associated with worse outcome after surgery for chronic subdural haematoma (CSDH). Only few studies have quantified outcomes specific to the very elderly or comatose patients. We aim to examine surgical outcomes in these patient groups. We analysed data from a prospective multicentre cohort study, assessing the risk of recurrence, death, and unfavourable functional outcome of very elderly (≥ 90 years) patients and comatose (pre-operative GCS ≤… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 26 publications
(57 reference statements)
2
17
0
Order By: Relevance
“…It has been shown that older patients have overall worse outcome after surgical treatment of cSDH. 3 Our data showed that patients ≥ 80 years old show higher complication and mortality rates. Hence, optimal surgical treatment is of paramount importance in geriatric patients.…”
Section: Discussionmentioning
confidence: 58%
“…It has been shown that older patients have overall worse outcome after surgical treatment of cSDH. 3 Our data showed that patients ≥ 80 years old show higher complication and mortality rates. Hence, optimal surgical treatment is of paramount importance in geriatric patients.…”
Section: Discussionmentioning
confidence: 58%
“…Chronic subdural hematomas (CSDHs) generally increase with age and are more prevalent in older patients, especial in individuals >65 years old ( 1 ). Although many risk factors may contribute to the occurrence of CSDHs, the pathogenic mechanisms underlying CSDH have remained unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic subdural hematomas (CSDH) generally increase with age and prevalent in older patients, especial in the population > 65 years old [1] . Many risk factors may contribute to the occurrence of CSDH, while the mechanism of CSDH is still unclear.…”
Section: Introductionmentioning
confidence: 99%